Exploring Factors Influencing Parent's Purchase Intention Towards Mathematics Educational Comics - Antoni, Tarisa Andika Putri (Integrasi Sains Media, 2024)
This research investigates the factors influencing parents' purchase intentions towards mathematics educational comics by expanding the Theory of Planned Behavior. Using a qualitative approach, the study conducted semi-structured interviews with ten parents of children in grades 1 to 3, selected through purposive sampling. The objective was to explore how various factors affect parents' decisions to purchase these educational materials. The study identifies several key characteristics that impact purchase intentions. Notably, teaching attributes such as the frequency and duration of use and parental attributes play a crucial role. The research also ranks the factors influencing purchase intentions in the following order: Perceived Behavioral Control, Attitude, Perceived Ease of Use, Perceived Value for Money, Subjective Norms, and Perceived Product Quality. This hierarchy reflects how parents prioritize these elements when deciding whether to invest in educational comics for their children. The findings suggest that Perceived Behavioral Control and Attitude are the most influential factors, highlighting the importance of how parents feel they can manage and benefit from the educational product. Perceived Ease of Use and Perceived Value for Money follow, emphasizing the need for user-friendly products that offer good value. Subjective Norms and Perceived Product Quality are also important but have a lesser impact than other factors. These insights are valuable for developing business strategies and marketing plans. By understanding and addressing these factors, companies can tailor their approaches to meet parents' needs better and enhance the appeal of mathematics educational comics.